2013
DOI: 10.5116/ijme.515a.2231
|View full text |Cite
|
Sign up to set email alerts
|

Ways in which healthcare organisations can support overseas-qualified doctors in the UK

Abstract: The full-text may be used and/or reproduced, and given to third parties in any format or medium, without prior permission or charge, for personal research or study, educational, or not-for-prot purposes provided that:• a full bibliographic reference is made to the original source • a link is made to the metadata record in DRO • the full-text is not changed in any way The full-text must not be sold in any format or medium without the formal permission of the copyright holders.Please consult the full DRO policy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…While shadowing and induction offer assistance at the beginning of the transition process, enhancing their mentorship through more frequent meetings with their supervisors and raising NHS staff awareness of IMG needs are also required. This model of more focused supervision of IMGs in their first year has also been supported by other studies 57…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While shadowing and induction offer assistance at the beginning of the transition process, enhancing their mentorship through more frequent meetings with their supervisors and raising NHS staff awareness of IMG needs are also required. This model of more focused supervision of IMGs in their first year has also been supported by other studies 57…”
Section: Discussionsupporting
confidence: 79%
“…Shadowing as a method of induction of new doctors is not a new strategy and has been used previously in the NHS, particularly for newly qualified doctors joining the UK foundation program with successful outcomes 9. Similar studies suggested that longer periods of shadowing are more beneficial than the short 1-week shadowing 7,9…”
Section: Discussionmentioning
confidence: 99%
“…They propose three elements of transition: cultural adjustment (process of acculturation and overcoming culture shock, also associated with non‐work factors), work adjustment (performance and feeling comfortable with the job) and interaction adjustment (being comfortable with interactions with host‐country nationals). These three areas are also evident in research into transition between health care contexts . Like the transfer of learning model, it too looks at individual and organisational factors that influence job performance.…”
Section: Methodsmentioning
confidence: 99%
“…For example, several participants have reported receiving inadequate or misleading information during their employment process. Providing devious information to newly arrived foreigners is unethical behavior ( Klingler and Marckmann, 2016 ; Rothwell et al., 2013 ). To overcome such challenges and to influence a transparent, and ethical employment process, United States has developed the "Alliance Code for Ethical Recruitment for Foreign-Educated Health Professionals".…”
Section: Discussionmentioning
confidence: 99%